Simultaneous Determination and Pharmacokinetics of Five Furocoumarins in Rat Plasma After Oral Administration of Radix Angelicae dahuricae Extract by High Performance Liquid Chromatography - Meng1, Yan; Zheng1, Xuguang; Cui4, Xiaohong; Sheng1, Ning; Wang1, Qiao; Wang1, Chunying; Zhang1, Lantong (Asian Journal of Chemistry, 2014)
Radix Angelicae dahuricae, with coumarins as its main bioactive compounds, has been widely used for antihistamine, antibacterial, spasmolysis, promote lipolysis and chronic venous insufficiency. Simultaneous determination and pharmacokinetics of coumarin compounds in rat plasma is necessary. A rapid, reliable and sensitive method for the simultaneous determination of 5 furocoumarins i.e., psoralen, bergapten, imperatorin, cnidilin and isoimperatorin in rat plasma was developed using high-performance liquid chromatographic. The established method could be easily applied to the determination in vivo and pharmacokinetic studies of five coumarin compounds in rat plasma after oral administration of Radix Angelicae Dahuricae extract.